Liberalizing Capital Flows and Managing Outflows : Background Paper. (Policy Papers; Policy Paper ;, 2012)
Liberalization of capital flows can benefit both source and recipient countries by improving resource allocation, reducing financing costs, increasing competition and accelerating the development of domestic financial systems. The empirical evidence, however, is mixed on the benefits, and it suggests that countries benefit most when they meet certain thresholds related to institutional and financial development. The principal cost of capital flow liberalization stems from the economic instability brought on by volatile capital flows. In extreme cases, sudden stops or reversals in capital inflows can trigger financial crises followed by prolonged periods of weak growth.